P273 MANAGEMENT OF ACUTE PULMONARY EMBOLISM IN GERIATRIC PATIENTS IN THE EMERGENCY ROOM: DOES ADHERENCE TO INTERNATIONAL GUIDELINES REDUCE IN ATYPICAL SYMPTOMS?. (18th May 2022) - Savioli, G; Lapia, F; Fumoso, F; Brattoli, M; Mugellini, A; Martignoni, A; Maggioni, P; Muzzi, A; Novelli, V; Preda, L; Lava, M; Manzoni, F; et al.
Abstract: Purpose of the Study: Evaluate if and how, in the real life of an Emergency Department, adherence to the Guidelines varies according to the presence of atypical symptoms. We understood dyspnoea, chest pain, signs and symptoms of deep vein thrombosis and syncope as typical symptoms. As atypical symptoms all the others (low–grade fever, vertigo …) Methods: Single–center retrospective observational study on all geriatric patients (>75 y) who entered our ED, where they received a diagnosis of acute PE. Enrollment began in 2016 and ended in 2019. We collected data from medical history, physical examination, laboratory tests, imaging; we calculated the characteristic scores from the diagnostic/therapeutic algorithm, both for the risk of PE (Wells, Geneva and YEARS), and for the presentation of the risk of mortality at 30 days (sPESI). We then analyzed adherence to the guidelines in three decision turning points: 1 Correct application of the decision scores examined, which classify the patient at low, intermediate or high risk of PE, calculated with Wells and simplified Geneva score; 2 Correct administration of therapy starting from ED as suggested by the guidelines; 3 Any observation in the care area of medium intensity with careful monitoring for the subpopulation of patients with evidence of right ventricular dilation or myocardial enzyme elevation (considered to be at high risk of shock and short–term mortality). Results: We enrolled 248 patients, with a mean age of 83 years with female prevalence (F = 63%). Of these, only 17 with atypical symptoms and 231 with typical symptoms. The vital signs were comparable in the two groups with no statistically significant difference (p > 0.05). Long–term outcomes such as mortality, need for hospitalization, hospitalization in intensive care and length of stay in hospital are also comparable results with no statistically significant difference (p > 0.05). However, adherence to international guidelines was statistically significantly lower in patients with atypical symptoms (33%) than in patients with typical symptoms (59%) (p < 0.05). Conclusions: The study suggests that patients with atypical symptoms are more likely to have reduced adherence to international guidelines, most likely due to diagnostic delay.